Proceedings of the 29th ACM International Conference on Information &Amp; Knowledge Management 2020
DOI: 10.1145/3340531.3412152
|View full text |Cite
|
Sign up to set email alerts
|

Feedback Loop and Bias Amplification in Recommender Systems

Abstract: Recommendation algorithms are known to suffer from popularity bias; a few popular items are recommended frequently while the majority of other items are ignored. These recommendations are then consumed by the users, their reaction will be logged and added to the system: what is generally known as a feedback loop. In this paper, we propose a method for simulating the users interaction with the recommenders in an offline setting and study the impact of feedback loop on the popularity bias amplification of severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(64 citation statements)
references
References 6 publications
(4 reference statements)
2
62
0
Order By: Relevance
“…When done properly, this would allow generating and studying feedback loops, like those created by reinforcement learning algorithms, but at a higher, more global level. As observed recently, and in agreement with our misinformation analysis [21], some algorithms are more prone to reproduce biases at each feedback loop [29].…”
Section: Open Questionssupporting
confidence: 91%
“…When done properly, this would allow generating and studying feedback loops, like those created by reinforcement learning algorithms, but at a higher, more global level. As observed recently, and in agreement with our misinformation analysis [21], some algorithms are more prone to reproduce biases at each feedback loop [29].…”
Section: Open Questionssupporting
confidence: 91%
“…Algorithms can also amplify already existing biases. For example, recommendation algorithms that are trained on the MovieLens data set 4 -a very popular data set in the research community-were found to strongly intensify the preexisting popularity bias they inherited from the data set [7,60].…”
Section: Discussion Of Underlying Reasonsmentioning
confidence: 99%
“…The numbers clearly indicate that a small fraction of the movies that are recommended on the front page accounts for a large number of the recorded page impressions. Interestingly, while recommender systems are often considered as means to increase sales in the long tail, the concentration on the short head can in fact be increased by a recommender system [36,48,60]. A popularity bias can be amplified by a recommender system when it learns from the recorded data to recommend popular items more frequently than less popular items.…”
Section: Description Of Undesired Effectsmentioning
confidence: 99%
“…In some cases, the problem is bias-related, and if there is a feedback loop (i.e. the model learns based on its previous predictions), the bias is aggravated in each new prediction made (Mehrabi et al 2019;Mansoury et al 2020). In other cases, the problem is related to the fact that the dataset evolves over time.…”
Section: Related Work In Robustness and Explainabilitymentioning
confidence: 99%